2013
DOI: 10.1176/appi.neuropsych.12120399
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Interleukin-6 Serum Levels in Acute Stroke

Abstract: The role of interleukin-6 (IL-6) as a risk factor for developing depressive symptoms, neuropsychological impairment, and related functional and neurological symptom severity during the acute phase of ischemic stroke is still underexplored. Here, the authors assessed this issue, in 48 patients without significant clinical history for major medical illnesses or other factors that promote inflammation, 72 hours after a first-ever acute ischemic stroke. In the acute phase of ischemic stroke, increased IL-6 plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…We found that vitamin D and IL‐6 were associated with the development of PSD. Similar to our result, low level of vitamin D has been considered as an important predicting factor for PSD (Han et al., ; Kaloglu et al., ) and IL‐6 has been showed to play a vital role in pathophysiology of PSD (Spalletta et al., ). Researchers have advanced one hypothesis that anti‐inflammatory role of vitamin D may play a role in the pathophysiology of PSD (Han et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…We found that vitamin D and IL‐6 were associated with the development of PSD. Similar to our result, low level of vitamin D has been considered as an important predicting factor for PSD (Han et al., ; Kaloglu et al., ) and IL‐6 has been showed to play a vital role in pathophysiology of PSD (Spalletta et al., ). Researchers have advanced one hypothesis that anti‐inflammatory role of vitamin D may play a role in the pathophysiology of PSD (Han et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…67–69 Elevated Il-6 is also implicated as an underlying mechanism for late-life depression; 7072 however, its role in late life apathy has yet to be examined. One study looking at depression among post-stroke individuals found that higher levels of Il-6 were associated with severity of apathetic-depressive symptoms, 73 indicating some evidence of an apathy-inflammatory link. Future studies should further explore this connection by examining apathy and inflammatory markers in the context of age-related motoric and functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Two review papers [90,91] provided evidence that proinflammatory cytokines, such as IL-1beta, TNF-alpha, or IL-18, resulting from stroke may lead to an amplification of the inflammatory process, widespread activation of 2,3-dioxygenase, and to a subsequent depletion of serotonin. Spalletta et al [92] performed an extensive neuropsychiatric evaluation of 48 ischemic stroke patients 72 h after the presentation of stroke symptoms and collected fasting peripheral blood for measurement of IL-6 at the same time point. Elevated serum IL-6 levels were associated with depressed mood, loss of interest, loss of weight/appetite, and insomnia.…”
Section: Post-stroke Fatigue and Depressionmentioning
confidence: 99%